"Water-In-Salt" Electrolyte For High Temperature Aluminum Ion Battery Application - Sylvia Ayu Pradanawati; Dinny Harnany; Faizal Fatah; Nur Layli Amanah (JMES The International Journal of Mechanical Engineering and Sciences, 2023)
This study focuses on examining aluminum chloride hexahydrate (AlCl3·6H2O) as an electrolyte salt in an Aluminum Ion Battery. The goal is to assess the effectiveness of AlCl3·6H2O as an electrolyte in an Aluminum Ion Battery, evaluate the battery's performance, and examine the anode and cathode properties of an Aluminum Ion Battery. Laboratory tests and literature analysis are the approaches used. Following cyclic voltammetry testing, it was shown that the water-in-salt electrolyte AlCl3 performed better than the 1M AlCl3 electrolyte. Compared to the 1M AlCl3 electrolyte, the hydrogen evolution reaction in the water-in-salt electrolyte AlCl3 has a smaller potential range. The cyclic voltammetry graph of an aluminum ion battery containing a water-in-salt AlCl3 electrolyte is noticeably smaller than that of an aluminum ion battery with a 1M AlCl3 electrolyte. It has been observed that the water-in-salt AlCl3 electrolyte requires more activation energy compared to the 1M AlCl3 electrolyte. Based on SEM-EDS data, using water-in-salt electrolyte AlCl3 for aluminum ion batteries is better as it does not cause significant defects in the anode and cathode.